What Drives Innovation in Family Farms? The Roles of Socioemotional Wealth and Diverse Information Sources - Fuetsch, Elena (European Journal of Family Business, 2022)
Family business literature barely addresses family farms and their innovation behavior. Innovation can be key to mitigate typical threats family farms are faced with, e.g., global competition and climate change. This article investigates socioemotional wealth (SEW) and diversity of information sources as innovation drivers. It also explores the role of diversity of information sources as a moderator. A sample of 911 family farms was used for linear regression analysis. The SEW dimension identification of the family members with the farm positively affects the implementation of innovation measures because the stronger the family members identify with the business, the more important is it for them to preserve the identity endowments. Since innovation is a way to do that, strong identification will motivate family members to innovate. Diversity of information sources is also positively linked to innovation measures. However, it has a negative moderating effect on the relationship between identification and innovation measures. While diverse information sources seem to increase a family farm’s ability to innovate by supporting the opportunity identification and utilization, it can also mitigate the farms willingness to innovate when information is ambiguous. The study integrates knowledge from agricultural, innovation and family business research and contributes to a better understanding of the peculiar business type “family farms” and SEW as a multidimensional concept.